Fake Daâ€™wah and Sectarianism: The Aftermath of Book Haram Conundrum on Islamic Education in Northern Nigeria (Journal of Governance and Development (JGD), 2014)
Daâ€™wah being an instrument of delivering the message of Islam has been used by some pugnacious self-acclaimed scholars to establish a religious wing in the name of preaching a dogmatic norm of Islam. Northern Nigeria has witnessed the activities of such nefarious elements, which culminated into a religious sect called â€œJamaâ€™atul Alhul Sunnah Liddaâ€™wati wal Jihadâ€ popularly known as Boko Haram. The article examines the vigorous Jihadist call by the sect for the establishment of an Islamic state in Nigeria, the aftermath of which has led to a deadly war that took more than five years and is still on going. The article examines the impact of the conflict on Islamic education in Northern Nigeria, particularly in the affected states. The research uses both doctrinal and qualitative methodologies in which interviews were conducted with respect to the effect of the Boko Haram on Islamic education. The article posits that the conflict initiated by Boko Haram has negatively affected daâ€™wah generally in northern Nigeria as every religious person who stands to preach Islamic precepts is perceived by the Nigerian security outfits as a potential Boko Haram member. This has deterred many Muslims from spreading or enlightening the Muslim Ummah, which consequently affects the dissemination of Islamic knowledge. The article further discloses the horrific consequences of the conflict on local informal and formal Islamic schools that usually teach Muslimsâ€™ children and youths the knowledge of their religion. All these problems are associated with fake daâ€™wah clerics and proliferation of religious sects associated with Islam. It is recommended that Muslims should stand to their obligation of respecting and protecting the ideals of Islamic religion devoid of personal sentiments. And the parties involved in the conflict should desist from attacking schools and maltreatment of Muslim scholars.